Endothelial nitric oxide synthase gene polymorphism is associated with systemic lupus erythematosus (2004)
Objective. In systemic lupus erythematosus (SLE), endothelial nitric oxide synthase (eNOS) gene locus has been found to be suggestive of linkage with disease, nitric oxide (NO) is produced in significant amounts, and endothelial cell dysfunction is observed. eNOS gene polymorphism may affect both the synthesis of eNOS protein and its enzymatic activity. We examined the influence of eNOS gene polymorphisms on susceptibility to SLE. Methods. Genomic DNA from 88 Northwestern Colombian women with SLE, as well as 199 controls matched for sex, age, and ethnicity, was genotyped for the –786T?C polymorphism in the promoter region, the intron 4 variable number of tandem repeats, and the Glu298Asp polymorphism in exon 7 of the eNOS gene by polymerase chain reaction and restriction fragment length polymorphism techniques. Haplotype and allele frequency comparisons, a Hardy-Weinberg equilibrium test, and linkage disequilibrium (LD) analysis were performed. Results. The intron 4b allele was associated with SLE (OR 2.2, 95% CI 1.29–3.60, pc = 0.005) as was the 4bb genotype (OR 2.9, 95% CI 1.61–5.33, pc = 0.0009), while the 4a allele was protective (OR 0.4, 95% CI 0.26–0.76, pc = 0.005), as was the 4ab genotype (OR 0.29, 95% CI 0.15–0.56, pc < 0.0001). In controls, all loci were in linkage disequilibrium (p < 0.02). In patients, intron 4 was in Hardy-Weinberg disequilibrium, due to an excess of homozygotes (p = 0.01). Conclusion. eNOS polymorphism influences SLE predisposition. Since intron 4bb genotype is responsible for higher levels of eNOS synthesis and intron 4 ab genotype is associated with lower synthesis, our results might provide insight into the elevated levels of NO observed in SLE patients.